Post-harvesting longevity of bird of paradise (Strelitzia spp.) treated with carnauba wax - Baudraz de Paula, Jean Carlo; Bonfante Rosalem, Isadora; Ribeiro Júnior, Walter Aparecido; Shimizu, Gabriel Danilo; de Faria, Ricardo Tadeu; de Andrade Pacheco, Camilla; Gonçalves de Oliveira Junior, Admilton (Comunicata Scientiae, 2021)
Strelitzias are tropical plants that have shown great interest in the market and can be used in landscaping in tropical floral arrangements. Aiming to extend its postharvest life, the objective of the work was to evaluate different concentrations of the commercial product based on carnauba wax in the postharvest longevity of Strelitzia juncea and Strelitzia reginae leaves. The experiment was conducted in a completely randomized design with five treatments and six repetitions, with one leaf per repetition for each species. The concentrations used were: 0% (control), 2%, 20%, 40% and 100%. The loss of leaf mass (%) and the visual quality of the leaves were evaluated through the criterion of notes, in addition to making use of anatomical analyzes of the stomatal structures of the leaves through scanning microscopy. The loss of mass was reduced with the increase of the wax concentration, however, high doses provided increased loss. The use of carnauba wax proved efficient at concentrations of 20 and 40%, maintaining the commercial quality of the leaves of S. reginae and S. juncea until the 24th day, while in the control treatment, the leaves maintained a commercial pattern until the 16th for S. reginae and 18th day for S. juncea. The deposition of wax in the stomatal structures may have influenced the loss of mass of both species as observed by scanning microscopy.